2021
DOI: 10.1108/jabs-12-2020-0471
|View full text |Cite
|
Sign up to set email alerts
|

Does “CHALTA HAI” culture negatively impacts sustainability of business firms in India? An empirical investigation

Abstract: Purpose Chalta hai (it is fine or it is acceptable) is an Indian cultural phenomenon that influences attitude towards work and business and diachronically adversely affects both. The purpose of this study is to explore its impact on the sustainability of business firms operating in India. Design/methodology/approach The research has firstly undertaken a theoretical study towards the development of appropriate hypotheses and a corresponding conceptual model, with emphasis on the effects of chalta hai culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 114 publications
0
12
0
Order By: Relevance
“…CSR activities could increase the reputation of the firms, thus affecting employee job satisfaction, organizational trust, and firm performance (Brammer et al, 2007;Lee et al, 2013;Sreenivasulu, 2019;Chatterjee et al, 2021a;Seifzadeh et al, 2021). Stakeholder theory posits that CSR initiatives could ensure success of a firm in the long run (Lee et al, 2019;Chatterjee et al, 2021b;Saxena et al, 2021). Carroll (1979) argued that a firm will exhibit its CSR towards society by carrying out its economic, legal, ethical, as well as philanthropic obligations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…CSR activities could increase the reputation of the firms, thus affecting employee job satisfaction, organizational trust, and firm performance (Brammer et al, 2007;Lee et al, 2013;Sreenivasulu, 2019;Chatterjee et al, 2021a;Seifzadeh et al, 2021). Stakeholder theory posits that CSR initiatives could ensure success of a firm in the long run (Lee et al, 2019;Chatterjee et al, 2021b;Saxena et al, 2021). Carroll (1979) argued that a firm will exhibit its CSR towards society by carrying out its economic, legal, ethical, as well as philanthropic obligations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stakeholder theory posits that CSR initiatives could ensure success of a firm in the long run (Lee et al. , 2019; Chatterjee et al. , 2021b; Saxena et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3.2 Electronic word of mouth eWOM is considered a mechanism through which customers across the world can express their opinions in online platforms about a product or a service (Cheung and Lee, 2012;Thrassou et al, 2021a). Social media is considered a convenient platform for providing feedback through ratings of a particular product or service.…”
Section: H3 Inu Has a Positive Impact On Individualism (Ind)mentioning
confidence: 99%
“…On the contrary side, Chatterjee et al (2021) investigated the casual nature of society toward sustainable practices and concluded that this casual behavior is deeply affecting India’s sustainable practices. It could be understood that the knowledge and responsibility of the society toward the idea of sustainability is minimal, which is not a desirable agenda.…”
Section: Literature Reviewmentioning
confidence: 99%